Istota współdziałania jednostek samorządu terytorialnego na gruncie prawa krajowego i międzynarodowego - Blicharz, Jolanta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The cooperation of self-government units in the form of national and international associations serves the exchange of experiences and implementation of good practices. It also creates the image of those units as being creative and open for development.
Keywords: territorial self-government; association; entity of territorial self-government; international association; collaboration